Resource sharing in LTE‐Advanced relay networks: uplink system performance analysis. Issue 1 (28th August 2012) - Bulakci, Ömer; Bou Saleh, Abdallah; Redana, Simone; Raaf, Bernhard; Hämäläinen, Jyri; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT Relay‐enhanced networks are expected to fulfil the demanding coverage and capacity requirements in a cost‐efficient way. Type 1 inband relaying has been standardised as an integral part of the Third Generation Partnership Project (3GPP) Long‐Term Evolution Release 10 and beyond (LTE‐Advanced). This type of relay nodes (RNs) supports a relaying mode where the RN to donor evolved node B (donor eNB, DeNB) link (relay link, a.k.a. backhaul link) transmission is time‐division multiplexed with the RN‐served user equipments (RUEs) to RN link (access link) transmission, whereas macrocell‐served user equipments (MUEs) share the same resources with the RNs at DeNB. Hence, system performance depends strongly on the resource sharing strategy among and within the links. Further, the set of subframes assigned for the relay link transmission is semi‐statically configured and thus a dynamic reconfiguration to adapt to fast‐changing system conditions (e.g. RN cell load) is not viable. Besides, in order to fully exploit the benefits of relaying, the inter‐cell interference, which is increased because of the presence of RNs, should be limited via a proper power control (PC) scheme on each link. Therefore, an optimisation of both the resource sharing and PC strategy is required to enhance the overall performance of relay networks. In order to tackle these issues, we employ a statistic‐based over‐provisioned backhaul subframe allocation to be utilised for flexible co‐scheduling of RNs and MUEs at the DeNB. In addition, we propose a combination of RN scheduling based on the number of RUEs and user throughput throttling achieving max–min fairness. Performance analysis of various resource sharing techniques along with PC optimisation is then carried out within the LTE‐Advanced uplink framework in urban and suburban scenarios. Comprehensive results show that the proposed schemes achieve significant throughput gains and high system fairness with substantially increased flexibility in resource allocation. Copyright © 2012 John Wiley & Sons, Ltd.